Variants near CHRNA3/5 and APOE have age- and sex-related effects on human lifespan - Joshi, Peter K.; Fischer, Krista; Schraut, Katharina E.; Campbell, Harry; Esko, Tõnu; Wilson, James F. (Nature communications, 2016)
Lifespan is a trait of enormous personal interest. Research into the biological basis of human lifespan, however, is hampered by the long time to death. Using a novel approach of regressing (272,081) parental lifespans beyond age 40 years on participant genotype in a new large data set (UK Biobank), we here show that common variants near the apolipoprotein E and nicotinic acetylcholine receptor subunit alpha 5 genes are associated with lifespan. The effects are strongly sex and age dependent, with APOE ɛ4 differentially influencing maternal lifespan ( P =4.2 × 10 −15 , effect −1.24 years of maternal life per imputed risk allele in parent; sex difference, P =0.011), and a locus near CHRNA3/5 differentially affecting paternal lifespan ( P =4.8 × 10 −11 , effect −0.86 years per allele; sex difference P =0.075). Rare homozygous carriers of the risk alleles at both loci are predicted to have 3.3–3.7 years shorter lives. Understanding the genetic influences on human aging requires a large number of subjects for a study of sufficient power. Here, Jim Wilson and colleagues use information on parental ages at death to show that common variants near the genes for apolipoprotein E and nicotinic acetylcholine receptor subunit alpha 5 are associated with longer lifespan.